Penggunaan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Prestasi Belajar Bahasa Inggris Materi Expressing Intention Pada Siswa Kelas X Teknik Kendaraan Ringan 3 Semester 1 SMKN 2 Gedangsari Gunungkidul Tahun Pelajaran 2017/2018 - Gunungkidul, Yogyakarta, Supiningsih SMK Negeri 2 Gedangsari, (Teknis, 2017)
This research is intended to improve learning achievement of English students by applying Problem Based Learning model of learning. The subjects of this study were students of Class X Lightweight Office Technique 3 which geared 32 students. Problem-Based Learning Object. The research method used is a classroom action research using two cycles in a sustainable manner. The technique data used are observation, documentation and test. The indicator of success in this study is something that improves students learning achievement that likes the applicable criteria Minimum Calculation Criteria (75) and at least 80% of learners can achieve the criteria of Minimum Criterion (75). Hypothesis of action in this research is the model of learning Problem Based Learning can improve student learning class X Lightning 3 Lighting Technique on English subject matter Reveals Intention. The conclusion of this research is the application of Problem Based Learning model of learning can improve learning achievement of class X students of Lightweight Office 3 Technique, which increase with the increase of class average from the initial condition 67,5 to 82,19 and the improvement of learning mastery from the initial condition 56.25% increased to 93.75%.Keyword : Problem Based Learning Learning Model, Learning Achievement, Expressing Intention.